Partial stab wound of renal pedicle. Segmental infarction of the kidney. Conservative treatment - Delgado, Bolívar (Cirugía del Uruguay, 2020)
The interest of this case lies in the infrequency with which the general surgeon must resolve this situation in the emergency...